Artistic practice and human experience - Simão, Luciano Vinhosa (PORTO ARTE: Revista de Artes Visuais, 2018)
In this article, I argue that the singularization of the artistic discourse in the 15th century encouraged philosophers in the 18th century to conceptualize on the aesthetic experience, taking it as a distinct kind of common experience. The description of this experience, as being one that is disinterested and lacks purpose, led to the progressive consolidation of an autonomous art, that is free from social contracts and takes refuge in museums. These have developed their physical space in accordance to this definitive presupposition. If, in contrast, we understand aesthetic experience as any complete experience, as Dewey sustains, our understanding of art and its institutions will be different.